2021
DOI: 10.3390/biom11121852
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Tetra-Adenylate (cA4) Recognition by Csa3; Implications for an Integrated Class 1 CRISPR-Cas Immune Response in Saccharolobus solfataricus

Abstract: Csa3 family transcription factors are ancillary CRISPR-associated proteins composed of N-terminal CARF domains and C-terminal winged helix-turn-helix domains. The activity of Csa3 transcription factors is thought to be controlled by cyclic oligoadenyate (cOA) second messengers produced by type III CRISPR-Cas surveillance complexes. Here we show that Saccharolobus solfataricus Csa3a recognizes cyclic tetra-adenylate (cA4) and that Csa3a lacks self-regulating “ring nuclease” activity present in some other CARF d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
(125 reference statements)
0
8
0
Order By: Relevance
“…Cell death [72] N od a t a TIR-SAVED TIR-SAVED >3 cOA 3 [87] NAD + [87] Cell death [87] N od a t a Csa3 CARF-HTH 1 cOA 4 [53] dsDNA [53] Transcriptional regulation [53] No [53] Csx1…”
Section: Csm6mentioning
confidence: 99%
See 1 more Smart Citation
“…Cell death [72] N od a t a TIR-SAVED TIR-SAVED >3 cOA 3 [87] NAD + [87] Cell death [87] N od a t a Csa3 CARF-HTH 1 cOA 4 [53] dsDNA [53] Transcriptional regulation [53] No [53] Csx1…”
Section: Csm6mentioning
confidence: 99%
“…The complete regulatory functions of these effectors appear to be very complex, but hints at cross-talk between type III and type I systems. It has been shown that Csa3 is involved in the regulation of type I CRISPR adaptation, as well as providing a feedback loop to type III interference [50][51][52][53][54]. Furthermore, Csa3-mediated activation of DNA repair genes has been demonstrated, indicating that the network of gene regulation by type III associated effectors might not be constricted to CRISPR-related genes [55].…”
Section: Coa-responsive Transcriptional Regulatormentioning
confidence: 99%
“…These positions correspond to the sites of cleavage of bound target RNA (46), which is catalysed by the Cas7-like backbone subunits (47)(48)(49).This activity is important for the dissociation of target RNA and deactivation of the Cas10 subunit (44,45). Previous studies showed that SsoCsm is unusual in not cleaving at one of the flipped sites, generating a spacing of 12,6,6,6 between sites (42). The missed cleavage corresponds to the Cas7b subunit (1432; chain N in the PDB file, Figure 3C, D), while subunits competent for RNA cleavage are Cas7a (1430, chain L in the coordinates file), Cas7c (1425, chains F and G) and Cas7d (1426, chains H and I).…”
Section: Fitting Colabfold Models Model Refinement and Analysismentioning
confidence: 99%
“…These ancillary nucleases typically have relaxed specificity and target both viral and host nucleic acids to slow down infection or cause abortive infection (11). The coordination of anti-viral responses at the transcriptional level by cA 4 are also possible (12).…”
Section: Introductionmentioning
confidence: 99%
“…These ancillary nucleases typically have relaxed specificity and target both viral and host nucleic acids to slow down infection or cause abortive infection ( Rostol and Marraffini, 2019 ). The coordination of anti-viral responses at the transcriptional level by cA 4 are also possible ( Charbonneau et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%